Emergency department visits for hemodialysis by insurance status in the United States. Issue 2 (19th April 2022) - West, Julianna; Chan, Hei Kit; Wang, Henry; Molony, Donald; Foringer, John; Huebinger, Ryan; Robinson, David; Chavez, Summer
Abstract: Objective: Many uninsured patients with end‐stage kidney disease (ESKD) depend upon the emergency department (ED) for hemodialysis (HD). We sought to characterize ED visits for emergent HD by insurance status. Methods: We performed a cross‐sectional analysis of the 2017 Nationwide Emergency Department Sample, including ED visits by patients ≥18 years old with a length of stay ≤1 day and performance of HD. Insurance status determined by "insured" as Medicare, Medicaid, or commercial and "uninsured" as self‐pay or charity. Results: Of 118, 034, 396 adult ED visits, 235, 988 were associated with HD: uninsured 62, 503 (incidence 5.30 per 10, 000, 95% confidence interval [CI]: 5.26–5.34) and insured 172, 889 (incidence 14.65 per 10, 000, 95% CI: 14.60–14.74). The south census region accounted for 89% of uninsured ED HD (odds ratio [OR] 31.55, 95% CI: 8.97–110.97). Compared to insured patients, uninsured ED HD patients were more likely to be younger (age 18–44, 37.6% vs 19.9%). The most common primary diagnosis for uninsured and insured ED HD patients was hypertensive chronic kidney disease (34.6% and 26.2%, respectively). Uninsured ED HD patients were less likely to be admitted (3.4% vs 36.0%, OR 0.06, 95% CI: 0.02–0.20). Most ED HD patients were discharged home (95.2% uninsured vs 57.6% insured). ED charges per visit were 5, 992.32 for uninsured and 10, 985.87 for insured ED HD patients. Conclusions: Our findings highlight the health care burden of ED HD. Novel system approaches are needed for the management of uninsured and insured patients with ESKD.